The Effect of Financial Ratio, Company Size, Previous Audit Opinion, and Auditor's Reputation on Going Concern Audit Opinion on Mining Companies Listed on the Indonesia Stock Exchange 2014-2018 - Wardani, Riski Fitri; Nadirsyah; Ridwan (International Journal of Economics (IJEC), 2024)
The Objective of this research is to examine and analyze the effect of financial ratios, company size, previous year's audit opinion, and auditor's reputation on going concern audit opinions on mining companies listed on the Indonesian stock exchange in 2014-2018. A total of 15 mining companies were studied in this study. The sample selection used purposive sampling method. Data were analyzed using logistic regression. The results obtained are simultaneously, liquidity, profitability ratios, leverage ratios, company size, previous year's audit opinion and auditor's reputation affect going concern audit opinions, while partially, liquidity ratios, profitability ratios, leverage ratios, company size and auditor's reputation s have no effect on going concern audit opinion. The previous year's audit opinion has an effect on going concern audit opinion.